Analysis Of The Effect Of Role Of Stress, Organizational Culture And Emotional Quotient On Employee Performance With Job Satisfaction As Intervening Variable At Royal Prima Medan Rsu - Muhammad Arviansyah, Shaid; Ria Ginting, Rasinta; Romy, Elly; Tribuana Sutanto, Alex (International Journal of Science, Technology & Management, 2022)
This study aims to partially test and analyze the effect of role of stress, organizational culture and emotional quotes on employee performance of medical and non-medical employees at RSU Royal Prima Medan, to examine and analyze the effect of job satisfaction on employee performance of medical and non-medical employees at RSU. Royal Prima Medan, tested and analyzed the effect of role of stress on job satisfaction of medical and non-medical employees, tested and analyzed the influence of organizational culture on job satisfaction of medical and non-medical employees, tested and analyzed the effect of emotional quotient on job satisfaction of medical and non-medical employees non-medical, testing and analyzing the influence of the role of stress on the employee performance of medical and non-medical employees, testing and analyzing the influence of organizational culture on the employee performance of medical and non-medical employees, as well as testing and analyzing the influence of emotion l quotient on employee performance of medical and non-medical employees at RSU Royal Prima Medan. This study uses a quantitative description of the questionnaire instrument, the population is 692 medical and non-medical people, the probability sampling technique is calculated using the Slovin formula so that the number of samples is 87 people. The data analysis technique used the instrument quality test, the use of classical assumptions, moderated linear regression, t test (partial) and F test (simultaneous), the coefficient of determination test.